2015
DOI: 10.1039/c4lc01018c
|View full text |Cite
|
Sign up to set email alerts
|

Capturing molecules with plasmonic nanotips in microfluidic channels by dielectrophoresis

Abstract: Over the last decades, different concepts have been established for the use of plasmonic nanostructures in sensing applications. One challenge in this context lies in delivering the analyte of interest to the location of the nanostructures and selectively attaching it to their surfaces. Here we present a method for the collection and concentration of molecules on arrays of metallic nanocones, making use of the high electric field gradients at the nanotips. For this purpose, the nanocones are integrated into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Another example is introduction of sheath-flow liquid focusing the sample solution to the SERS substrate [85]. An elegant way of sample capturing is the use of dielectrophoretic field generated at the substrate as described by Schäfer et al using plasmonic substrate of gold nanotips for creation of dielectrophoretic field for selective molecule capturing [86].…”
Section: Strategies For Nanoparticles Immobilizationmentioning
confidence: 99%
“…Another example is introduction of sheath-flow liquid focusing the sample solution to the SERS substrate [85]. An elegant way of sample capturing is the use of dielectrophoretic field generated at the substrate as described by Schäfer et al using plasmonic substrate of gold nanotips for creation of dielectrophoretic field for selective molecule capturing [86].…”
Section: Strategies For Nanoparticles Immobilizationmentioning
confidence: 99%
“…[34][35][36] Some of these modeling studies [21,[33][34][35][36] have observed temperature inhomogeneities in conical structures with dimension over the diffraction limit (µm-long tips), where the inhomogeneities are usually considered negligible to affect the addressed applications. [22,24] Similarly, recent sensing applications [30,37] based on arrays of ≈100 nm-long nanocones [38][39][40] have leveraged on the excitation of the characteristic EM hotspots of the nanocones while the study of their associated thermoplasmonic response was not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, carbon nanotubes have been grown on flat electrodes to increase capture of titanium dioxide (TiO 2 ) nanoparticles using DEP . In another study, nanometer sized cones were used to trap BSA molecules using DEP .…”
Section: Introductionmentioning
confidence: 99%